Analisis Kompetensi SDM, Kapasitas SDM, Pemanfaatan Teknologi Informasi, dan Pengendalian Intern Akuntansi Terhadap Keterandalan Informasi Pelaporan Keuangan BKAD (Studi pada BKAD Kota Malang) - Sadewo, Zyudha Syafa; Mahsuni, Abdul Wahid; Junaidi, Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2024)
The purpose of this study is to ascertain whether information technology, internal accounting control, human resource competency, and human resource capacity affect the dependability of financial information. This study used questionnaires as a means of data collecting, making it a quantitative research design. The Regional Financial and Asset Agency is the study's population, and the sample was chosen using the purposive sampling technique—a method that involves choosing research samples based on predetermined criteria in order to achieve particular goals. Multiple Linear Regression analysis is the technique utilized for analysis. Following data analysis, the research findings utilizing the F-test and t-test show that internal accounting control, information technology, and human resource competency are all influenced. The human resource capacity variable, however, has no bearing. Keywords: Human resource competencies, human resource capacity, information technology, internal accounting control, reliability of financial report information